2014
DOI: 10.3144/expresspolymlett.2014.84
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the production of FRP composites: A review of in-line sensing methods

Abstract: Abstract.Composites manufacturing is characterized by many degrees of freedom. Different materials, geometries and thermo-dynamical conditions contribute to a behavior that is difficult to predict. Monitoring the running process (in-line monitoring) eliminates the need for prediction; real time data provided by appropriate sensing systems can be used in the direction of process optimization, quality upgrade or material characterization. The aim of the review at hand is to record and discuss the latest progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 75 publications
0
75
0
1
Order By: Relevance
“…A range of optical techniques have been investigated for composite material processing, with demonstrations of the ability to detect the presence of resin using a single sensor [20,21], to measure resin flow during the infusion when the sensors are spatially multiplexed [14,22], and to monitor the cure of the resin [11,21,22]. Superimposed fibre grating sensors, offering strain-temperature discrimination, have also been demonstrated for cure monitoring [23].…”
Section: Ultrasonic Sensorsmentioning
confidence: 99%
“…A range of optical techniques have been investigated for composite material processing, with demonstrations of the ability to detect the presence of resin using a single sensor [20,21], to measure resin flow during the infusion when the sensors are spatially multiplexed [14,22], and to monitor the cure of the resin [11,21,22]. Superimposed fibre grating sensors, offering strain-temperature discrimination, have also been demonstrated for cure monitoring [23].…”
Section: Ultrasonic Sensorsmentioning
confidence: 99%
“…The tool supports heating by liquid that flows through heating channels opened in the tool body while it was designed to host different sensors, namely dielectric analyzer, direct current sensor, ultrasound sensor, and pressure transducers. All of the above detect (among other quantities) flow 17 but technical…”
Section: Computational Aspectsmentioning
confidence: 99%
“…Therefore, the use of real‐time in‐mold sensors to monitor the material behavior and process conditions have continuously been a research topic over the last years . Dielectric analysis (DEA) has been evaluated as the technology with the greatest potential for in‐situ material characterization during the cure of an epoxy resin . Previous studies also showed that phase transitions of a two‐step‐curing polyurethane resin for pultrusion processing and of carbon fiber‐reinforced thermoplastic materials can be distinguished by DEA .…”
Section: Introductionmentioning
confidence: 99%